Molecular detection of Helicobacter pylori based on the presence of cagA and vacA virulence genes in dental plaque from patients with periodontitis - Carlos Eduardo Flores-Treviño; Víctor Hugo Urrutia-Baca; Ricardo Gómez-Flores; Myriam Angélica De La Garza-Ramos; María Marisela Sánchez-Chaparro; Mario Alberto Garza-Elizondo (Journal of Dental Sciences, 2019)
Background/purpose: Helicobacter pylori (H. pylori) infection is the most common in the world and is associated with various gastrointestinal pathologies, including chronic gastritis, peptic ulcers, and gastric cancer. The prevalence is associated with socioeconomic conditions, with this infection being more common in developing countries than in developed countries. The presence and permanence of H. pylori in the oral cavity has been reported, but its role is controversial. The aim of this study was to determine the prevalence of H. pylori in dental plaque of patients with periodontitis. Materials and methods: A cross-sectional study was carried out and Periodontal Screening and Recording (PSR) index was determined. 38 dental plaque samples were taken and total DNA was extracted and qPCR was performed. Results: 60.5% of the samples (n = 23) were positive for the presence of H. pylori by the amplification of the 16S rRNA and vacA genes. In addition, cagA gene was detected in 21.7% (n = 5) of H. pylori-positive. A significant relationship between periodontal status and H. pylori oral infection was found (P ≤ 0.05); patients with initial and moderate periodontitis were the most affected with 39.1% and 30.4%, respectively. Conclusion: Our results suggest that the prevalence of H. pylori in the oral cavity could be related to the progression of periodontal disease. Therefore, oral hygiene and treatment for the elimination of oral H. pylori could stop the progression of periodontal disease. Keywords: Helicobacter pylori, cagA, vacA, Oral cavity